2010
DOI: 10.1007/s10597-010-9367-4
|View full text |Cite
|
Sign up to set email alerts
|

The Experts Rate: Supervisory Behaviors That Impact the Implementation of Evidence-Based Practices

Abstract: The purpose of this study was to identify the critical behaviors of supervisors for the successful implementation of evidence-based practice in adult mental health. Experts who work with supervisors to support implementation in three evidence-based practices were surveyed. The three evidence-based practices included Assertive Community Treatment, Integrated Dual Diagnosis Treatment, and Supported Employment. There was substantial agreement among experts as to the importance of supervisory behaviors in the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…High turnover rates among mental health providers are problematic for high quality services. Research emphasizes the roles of supervisors as critical determinants of quality practices (Carlson, Rapp, & Eichler, 2012); however, formal supervision tends to be infrequent, and in standard practice, the attention to supervision varies. Using longitudinal mediation analyses, our study identified the effect of supervisory support on reduced turnover intention through reduced exhaustion.…”
Section: Resultsmentioning
confidence: 99%
“…High turnover rates among mental health providers are problematic for high quality services. Research emphasizes the roles of supervisors as critical determinants of quality practices (Carlson, Rapp, & Eichler, 2012); however, formal supervision tends to be infrequent, and in standard practice, the attention to supervision varies. Using longitudinal mediation analyses, our study identified the effect of supervisory support on reduced turnover intention through reduced exhaustion.…”
Section: Resultsmentioning
confidence: 99%
“…Psychology training programs promote evidencebased practice (EBP), which has been defined as "the integration of the best available research with clinical expertise in the context of patient characteristics, culture, and preferences" (APA, 2006, p. 475). Supervisors play a key role in teaching trainees EBP skills and supporting trainees in their adherence to EBP (Bearman et al, 2013(Bearman et al, , 2017Carlson, Rapp, & Eichler, 2012). There is wide recognition that clinical supervision is essential to the attainment of practitioner competencies (Gonsalvez & Milne, 2010;McCutcheon, 2009;Milne & Watkins, 2014;Scott, Pachana, & Sofronoff, 2011).…”
Section: Evidence-based Practice and The Scientist-practitioner Modelmentioning
confidence: 99%
“…Several studies provide evidence for the effectiveness of live supervision , case presentations (Hadjistavropoulos, Kehler, Peluso, Loutzenhiser, & Hadjistavropoulos, 2010), case formulations (Page, Stritzke, & Mclean, 2008), supervisor modelling and role play (Beidas & Kendall, 2010), video feedback (Gonsalvez, Brockman, & Hill, 2016;Hill, Crowe, & Gonsalvez, 2015), and evidence-based feedback (O'Donovan, Halford, & Walters, 2011). Supervision involving these active learning techniques are more effective than discussion of specific EBP practices (Accurso et al, 2011;Bearman et al, 2013;Beidas, Edmunds, Marcus, & Kendall, 2012;Carlson et al, 2012;Dorsey et al, 2018). With overwhelming theoretical support for SP models in psychology training, one would expect that practice would reflect a faithful adherence to EBP among psychology practitioners.…”
Section: Supervisory Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…A review and national survey of 42 Mental Health Trusts in UK on the disciplinary composition of community mental health teams suggested that rather than offering services mainly based on the existing professional mix with no clear workforce planning, the workforce needed to be organized to best fulfilling local needs (Evans et al, 2012). Another survey of 45 ICMHS experts found that supervisory behaviours were important in building and enhancing staff skills, facilitating team meetings, and leading continuous quality improvement activities that might enhance the implementation of evidence‐based ICMHS (Carlson, Rapp, & Eichler, 2012). A mixed methods study was conducted to evaluate the introduction of a support worker to the community mental health team for older adults, involving a survey of 28 staff members from four teams, 27 individual interviews of support and professional workers, and a focus group interview of four support and two professional workers over 18 months (McCrae, 2008).…”
Section: Introductionmentioning
confidence: 99%